Process intensification connects scales and disciplines towards sustainability - Boffito, Daria C.; Fernandez Rivas, David (Canadian journal of chemical engineering, 2020)
Process intensification (PI) has been established as a cluster of technologies able to produce more with less. While scientists around the globe advocate for new semantics that are increasingly tied to the notion of sustainability, what does the literature data say about PI? A Vosviewer bibliometric map of PI displays it as closely linked to the subjects of design, optimization, gas‐to‐liquid technologies, mass transfer, catalysis, and kinetics. We analyze the relationship between PI and these subjects while identifying misconceptions about the intensifying potential of some of them, as is the case for process optimization. We provide examples and summarize the recent technological trends for all these cases. Finally, we provide an outlook on the future of PI in which we identify elements that will be key to accelerate the adoption of PI technologies at the commercial scale.